1997
DOI: 10.1016/s0009-9236(97)90085-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant pharmacodynamics on lymphocytes from healthy subjects and patients with chronic renal failure, nephrosis, and psoriasis: Possible implications for individual therapeutic efficacy*

Abstract: A large subset of patients with chronic renal failure showed PBMC resistance to cyclosporine and prednisolone. Hyperresistant patients have a high risk of being refractory to immunosuppressive therapy with one of these drugs. Alternative treatment should be considered according to the individual drug-sensitivity data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 33 publications
4
71
2
Order By: Relevance
“…In most cases, the drug is useful in suppressing severe clinical symptoms of AD; however, individual variations in tacrolimus efficacy, adverse effects from tacrolimus including skin burning, pruritus, varicella and blisters [40], and/or recurrence of AD after cessation of tacrolimus use have been reported. Pharmacodynamic approaches with the use of PBMCs of the patients could be an efficient strategy for the evaluation of the individual therapeutic potentials of tacrolimus, as has been shown for cyclosporine use in the treatment of psoriasis [41] and GC use in kidney transplantations [23, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the drug is useful in suppressing severe clinical symptoms of AD; however, individual variations in tacrolimus efficacy, adverse effects from tacrolimus including skin burning, pruritus, varicella and blisters [40], and/or recurrence of AD after cessation of tacrolimus use have been reported. Pharmacodynamic approaches with the use of PBMCs of the patients could be an efficient strategy for the evaluation of the individual therapeutic potentials of tacrolimus, as has been shown for cyclosporine use in the treatment of psoriasis [41] and GC use in kidney transplantations [23, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…This 20 ml sample size was the smallest possible to carry out the drug sensitivity tests for four immunosuppressive agents, but occasionally not all four of these agents could be tested for each subject. The heparinized blood was loaded on 3 ml of Ficoll-Hypaque (Nakarai Co., Japan), centrifuged at 1300 Ă—g for 20 min, and PBMCs were separated as described previously [4][5][6]21]. For the evaluation of PBMC-sensitivity to immunosuppressive drugs, cells were washed and suspended in RPMI 1640 medium containing 10% fetal bovine serum, 100,000 IU/l penicillin, and 100 mg/l streptomycin to a final density of 1Ă— 10 6 cells/ml.…”
Section: Isolation Of Pbmcs and Evaluation Of Drug Effects In Vitromentioning
confidence: 99%
“…However, variations in the clinical efficacy of the drugs in individual patients have been observed, and patients with poor responses to the drugs have required long-term or relatively high doses and thus experience serious side effects with less improvement in their conditions [1]. One of the attractive ways to predict the clinical efficacy of immunosuppressive drugs in individual patients is the cellular pharmacodynamics of drugs using PBMCs of patient origin [4][5][6]. It has been reported that the in vitro response of PBMCs to the suppressive effects of immunosuppressive drugs correlate with clinical efficacy in asthma [7], renal transplantation [5,8], minimal change nephrotic syndrome [5,6], psoriasis [4], rheumatoid arthritis [9], and ulcerative colitis [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Periodic immune monitoring using each patient's peripheral lymphocytes would be useful to individually optimize immunosuppressive drug therapy. 4,5 The lymphocyte adenosine triphosphate (ATP) assay is an in vitro diagnostic method, used to evaluate the immune status, that uses samples of whole blood stimulated with phytohemagglutinin.…”
Section: Introductionmentioning
confidence: 99%